The role of lung structure and function in adaptation to high altitude deer mice (Peromyscus maniculatus) - West, Claire (My University, 2020)
High altitude environments present two main stressors: 1) low levels of oxygen and 2) low temperatures. For small endotherms, this is especially challenging, as they have to generate heat to maintain their body temperature. Lowland animals that travel to high altitude are often faced with maladaptive responses to hypoxia (e.g., hypoxic pulmonary hypertension), while the same responses are not seen in highland natives. Using North American deer mice (Peromyscus maniculatus), we investigated whether highlanders and lowlanders had different responses to chronic hypoxia exposure (12 kPa O2, simulating the O2 pressure at 4300 m for 6-8 weeks). In response to chronic hypoxia, lowlanders show hypoxic pulmonary hypertension (HPH; increases in right ventricle systolic pressure), thickening of pulmonary arterial smooth muscle, and right ventricle hypertrophy. In contrast, highlanders showed attenuated HPH and no associated changes in pulmonary arterial structure or right ventricle hypertrophy. Both highlanders and lowlanders were able to maintain V-Q matching in chronic hypoxia, but highlanders show increased in vivo lung volume after chronic hypoxia. Overall, evolved changes in lung function help attenuate maladaptive plasticity and contribute to hypoxia tolerance in high-altitude deer mice.
Keywords: Deer mice; High altitude; hypoxia; V-Q matching